THE IMPACT OF THE EXISTENCE OF FISH AUCTION PLACE (TPI) ON INFRASTRUCTURE DEVELOPMENT AND SOCIO-ECONOMIC CONDITIONS OF COMMUNITIES IN SUMPANG BINANGAE VILLAGE, BARRU DISTRICT - Amrianah, Herlina; Pratiwi, Dian; Hamal, Muh.Rizal (P3M Stia Al Gazali Barru and Meraja media, 2023)
Copyright (c) 2023 Meraja journal Downloads